Evaluating the impact of peer feedback on student presentations - Plank, Barbara (Improving University Science Teaching and Learning, 2023)
The aim of this project is to restructure the course Cognitive Science 1 that I taught in autumn 2015 at the Humanities faculty at the University of Copenhagen. In particular, given my reflections on last year’s evaluation, I wanted to increase the benefit of student oral presentations by evaluating the effectiveness of peer assessment. The effect was evaluated through a questionnaire in the middle of the course, overall peer feedback response rate, the course evaluation and a focus interview at the end of the course. Peer feedback was overall considered beneficial, but enough time needs to be allocated for it during class.